Language Variation in Video Games: A reception study on the impact of Anne Bonny’s language variation on the gameplay experience of Assassin’s Creed: Black Flag in English and Brazilian Portuguese - Deretti, Amábile Alice (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
This study aims to identify the reception of the Irish English localisation into Brazilian Portuguese in the video game Assassin’s Creed: Black Flag by analysing the gameplay experience of Brazilian gamers living in Ireland. This study first analyses how Irish English is portrayed in the game, followed by a survey on the gameplay experience. The analysis was performed by phonetic transcription of the linguistic features that resemble the Irish language variation. The gameplay experience involved four Brazilian gamers living in Ireland, where the participants played the game in two in-person sessions. At the same time, the researcher followed the gameplay and made notes on their reactions through a Think-aloud Protocol. A questionnaire followed this session. Results show that the gameplay experience in TT is negatively affected by the voice performance and linguistic features implemented in the localised version, even though the players still managed to feel relatively immersed in the game while playing the localised version.
Keywords: Literary Translation